بررسی ارتباط مصرف قلیان با سرطان ریه - حسامی, زهرا; آریانپور, مهشید; حسامی, افشین; شیخ زاده, حکیمه; سبحانی, سوگل (فصلنامه نفس, 2023)
Introduction Considering that Tobacco smoking is one of the main risk factors for lung cancer, many studies have been conducted in this field but there are few studies on the relationship between hookah and this type of cancer. In this study the relationship between water pipe smoking and lung cancer was evaluated. Method This case control study has been done on 70 hospitalized cases with diagnosed lung cancer in Massih Daneshvari hospital and 70 healthy individuals as control group who were matched with the patients in terms of age and sex. Data collection was a standard questionnaire. Statistical analysis was done by SPSS software. Results: 134 participants (65 in case group and 69 in control group) participated in the study). The mean age of the case group was 59.7 SD=9 and the mean age of the control group was 58.5±9. Seven patients (11.1%) were hookah user and in the control group, 4 (6.05%) were hookah user. p<0.001 In case group 38(58. 5%) persons were cigarette smokers compare with 29(31. 9%) cigarette smokers in the control group . p=0.001 Conclusion: According to the results, there is significant relationship between Hookah smoking and lung cancer. Considering increase water pipe smoking, among people this type of tobacco smoking could be a main risk factor for lung cancer.